2017
DOI: 10.1080/19420862.2017.1345834
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of an intracerebroventricularly administered antibody in rats

Abstract: The pharmacokinetics (PK) of an antibody in the brain and the spinal cord is insufficiently understood, which is an obstacle to the discovery of antibody drugs that target diseases in the central nervous system. In this study, we focused on the elimination of IgG from cerebrospinal fluid (CSF) circulating in the brain and the spinal cord in rats, and, to evaluate the influence of CSF bulk flow on the clearance of IgG, also examined the PK of inulin in CSF. To monitor their concentrations in CSF, IgG and inulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
(21 reference statements)
3
21
0
Order By: Relevance
“…2A). This is in line with the documented half-life of antibodies in the CSF of 1 to 2 days [10,11]. Intravenous application of anti-Nogo A antibodies resulted in high values after the first and second bolus injections ( Fig.…”
Section: Resultssupporting
confidence: 86%
“…2A). This is in line with the documented half-life of antibodies in the CSF of 1 to 2 days [10,11]. Intravenous application of anti-Nogo A antibodies resulted in high values after the first and second bolus injections ( Fig.…”
Section: Resultssupporting
confidence: 86%
“…5a, b). Noteworthy, after 24 h from ICV administration, αCXCL13 mAb was present in the spinal cord parenchyma ( Supplementary Figure 5a-d ) of 129Sv-mSOD1 mice and in microvessels surrounding MNs ( Supplementary Figure 5e-g ) suggesting that αCXCL13 mAb crossed the blood-brain barrier or is cleared via bulk flow and transferred to blood circulation due to the CSF turnover [41] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that a divalent siRNA has broad distribution and activity in the CNS of NHPs including neurons and GFAP positive astrocytes ( 50 ). In contrast to ASOs and divalent siRNAs, intrathecal delivery of other drug modalities such as antibodies, proteins or peptides results in a large rostral to caudal gradients and limited accumulation in tissue ( 51 , 52 ). Viral delivery of gene therapy achieves good CNS distribution but does not effectively target non-neuronal cells ( 53 ).…”
Section: Discussionmentioning
confidence: 99%